Xiaoyao powder alleviates the hippocampal neuron damage in chronic unpredictable mild stress-induced depression model rats in hippocampus via connexin 43Cx43/glucocorticoid receptor/brain-derived neurotrophic factor signaling pathway. Issue 1 (1st January 2022) - Zhang, Yuanyuan; Luo, Yong; Hou, Xuenan; Lu, Kang; He, Yanhong; Yang, Baoying; Qin, Yi
ABSTRACT: Xiaoyao Powder (XYP) has been widely applied in China to treat stress-related illnesses, such as migraine, depression, Parkinson's disease, insomnia, and hypertension. Herein, this study aims to explore the effect of XYP on chronic unpredictable mild stress (CUMS)-induced depression and its underlying mechanisms. CUMS-induced depression rat models were established, they were subsequently randomly divided and treated with various conditions. Results of this study indicated that supplementation of XYP observably abolished CUMS-induced hippocampal damage and serum corticosterone (CORT) elevation. In mechanism, we discovered that CUMS induction could cause a prominent downregulation in glucocorticoid receptor (GR), phosphorylated-GR (p-GR), connexin 43 (Cx43), and brain-derived neurotrophic factor (BDNF), a remarkable upregulation in c-Src. While the introduction of XYP could reverse the changes in all of these indicators mediated by CUMS. Furthermore, we proved that Cx43 could interact with GR, and the protective effect of XYP on hippocampal neurons is realized by up-regulating GR. Summarized, this study indicated that XYP could ameliorate hippocampal neuron damage in CUMS-induced depression model rats through acting on Cx43/GR/BDNF axis.